2018
DOI: 10.1002/awwa.1048
|View full text |Cite|
|
Sign up to set email alerts
|

Pilot‐Scale Removal of Total and Hexavalent Chromium From Groundwater Using Stannous Chloride

Abstract: Alternative processes for hexavalent chromium (Cr(VI)) removal from drinking water continue to be of interest for utilities despite the existence of several established technologies. Stannous chloride (SnCl 2 ) can reduce Cr(VI) to trivalent chromium, but research has been limited, especially related to the filterability of total chromium (Cr(T)) following reduction. At the pilot scale, SnCl 2 was tested over a range of doses in three ground-waters with naturally occurring Cr(VI) concentrations ranging from 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…A groundwater well in central Oklahoma with a naturally occurring and relatively high Cr(VI) concentration was chosen for this study, the same water designated as OK in Kennedy et al (). As shown in Table , the Cr(T) concentration, predominately present as Cr(VI), averaged 0.090 ± 0.005 mg/L (average ± standard deviation) over the course of the study, nearly nine times the previously rescinded California Cr(VI) MCL (State Water Resources Control Board, ) and close to exceeding the USEPA Cr(T) MCL.…”
Section: Methodsmentioning
confidence: 99%
“…A groundwater well in central Oklahoma with a naturally occurring and relatively high Cr(VI) concentration was chosen for this study, the same water designated as OK in Kennedy et al (). As shown in Table , the Cr(T) concentration, predominately present as Cr(VI), averaged 0.090 ± 0.005 mg/L (average ± standard deviation) over the course of the study, nearly nine times the previously rescinded California Cr(VI) MCL (State Water Resources Control Board, ) and close to exceeding the USEPA Cr(T) MCL.…”
Section: Methodsmentioning
confidence: 99%
“…Pilot testing of RCF with stannous as an alternative reductant, in lieu of ferrous, resulted in complete Cr removal and extended filter run time, with stannous resulting in more than double the unit filter run volume than that of ferrous (Gorman, Plummer, Samson, Townsend, & Seidel, 2019). Stannous pilot testing conducted by Kennedy et al (2018) on Cr(VI)-reduced waters also demonstrated Cr removal with sand filtration, although little or no Cr removal occurred with depth or pleated cartridge filtration. Kennedy et al (2018) used a stannous stock solution made from reagent-grade SnCl 2 with diluted deionized water that resulted in a pH of~2, which is in the pH range where stannic hydroxide can form and precipitate out of solution (Al-Hinai, Al-Hinai, & Dutta, 2014).…”
Section: Sncl 2 Overviewmentioning
confidence: 96%
“…Stannous pilot testing conducted by Kennedy et al (2018) on Cr(VI)-reduced waters also demonstrated Cr removal with sand filtration, although little or no Cr removal occurred with depth or pleated cartridge filtration. Kennedy et al (2018) used a stannous stock solution made from reagent-grade SnCl 2 with diluted deionized water that resulted in a pH of~2, which is in the pH range where stannic hydroxide can form and precipitate out of solution (Al-Hinai, Al-Hinai, & Dutta, 2014). Throughout their testing, stability issues were observed, and the diluted stock was regularly remade because, as the stock age increased, its Cr(VI) reduction potential decreased, it gained a yellow color, and turbidity increased, indicating that Sn(II) was oxidized in air-saturated water and precipitated out of solution.…”
Section: Sncl 2 Overviewmentioning
confidence: 96%
See 2 more Smart Citations